Electrical, Thermal, and Structural Characterization of Plant-Based 3D Printed Gel Polymer Electrolytes for Future Electrochemical Applications - Muhammad Afiq Hazizi Mahamood; Muhammad Faishal Norjeli; Ahmad Adnan Abu Bakar; Shahino Mah Abdullah; Nizam Tamchek; Ikhwan Syafiq Mohd Noor; Ala H. Sabeeh; Ahmad Fudy Alforidi; Ibrahim H. Khawaji; Mohd Ifwat Mohd Ghazali (MDPI, 2024)
Volume 15 Issue 24